Knowledge, Attitude, and Barriers Influencing Seasonal Influenza Vaccination Uptake - Mazin A. Barry; Khalid I. Aljammaz; Abdulaziz A. Alrashed (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Seasonal influenza is an acute respiratory infection caused by influenza viruses that are highly contagious and circulate in all parts of the world. It gives rise to an estimated 3 to 5 million cases of severe illness and about 250,000 to 500,000 deaths globally each year. Influenza tends to cause epidemics with serious illness and death among high-risk groups such as children aged 5 years and younger, pregnant women, elderly ≥65 years of age, and with chronic medical conditions. According to the Centers for Disease Prevention and Control (CDC), all people who are 6 months old and above are recommended to receive the seasonal influenza vaccine annually. Despite the fact that influenza vaccine is readily available, and the severity of the disease is known to adversely affect the individual’s quality of life and well-being, vaccination uptake rates are still low, contributing to the increased burden of the disease worldwide. Objectives. To measure the influenza vaccine uptake among residents of Riyadh Province, Saudi Arabia, that determines their attitude, knowledge, and beliefs regarding the vaccine. Methods. A cross-sectional study was conducted using a self-administered structured questionnaire distributed online targeting residents of Riyadh Province, Saudi Arabia, from 1st of August 2019 till 30th of September 2019. Participants were selected through volunteer sampling. The questionnaire included demographic data including age, gender, occupation, education level, marital status, and comorbidities. It also included questions regarding knowledge, attitude, and beliefs regarding influenza vaccine. After collection of data, statistical analyses were conducted by using Statistical Package for Social Sciences (SPSS) version 19.0. A P value of <0.05 was considered statistically significant. Results. Our study included 503 participants, with age ranging from 18 to 65 years old and 324 (64%) were females. 100 participants (19.9%) had comorbid conditions, and 223 (44.3%) have been vaccinated against influenza in the past. A large portion of participants (41.2%) were familiar with seasonal influenza vaccination from the media. The knowledge part of the questionnaire showed that 302 (60%) participants knew how often they should receive the vaccine and 313 (62.2%) participants knew that the vaccine is provided freely in all of Saudi Arabia. In terms of belief and attitude, 371 participants (73.8%) thought they were susceptible to the disease and 365 (73.8%) believed that influenza vaccine is beneficial, while 446 participants (88.7%) thought that the general public need more knowledge and awareness on the scientific facts of influenza vaccine. Regarding barriers, 295 participants (58.6%) wanted to avoid vaccines and 252 (50.1%) were concerned about the vaccine’s adverse effects. Participants with frequent health checkups and those who had previous knowledge on the availability of the vaccine for free were more likely to be vaccinated. Vaccinated participants (44.3%) were asked if they were willing to take the vaccine again when it is due, 158 (70.9%) answered yes. Those who elicited symptomatic reaction to the vaccine (26.0%) were less inclined to take it again P=0.035. Conclusion. We concluded that there is a low influenza vaccine uptake rate among our study population, considering that the barriers most commonly chosen by participants are solvable with health education and campaigns oriented towards delivering facts about the vaccine and dispelling misinformation; such measures are highly recommended and are postulated to carry a great benefit that should target common misconceptions identified in this study.